Employees buying organic food intention: An extension of the theory of planned behavior - Jiang, MengMeng; Wu, Qiong (Frontiers in Psychology, 2022)
A gradual increase in population and urbanization has increased the demand for global resources, which ultimately burdens the depletion of resources and challenges environmental sustainability worldwide. In recent decades nature sustainability has been the biggest challenge encountered by humankind. In addition, the changing lifestyle and consumption patterns have enormously played a key role. However, the consumption pattern from the employee's perspective suffers from the lack of research. Therefore, grounded on the theory of planned behavior (TPB), this research explores the antecedents and consequences of employees' buying intentions in the world's emerging market (China). Data were collected using a web-based link shared via WeChat and Q.Q.; resultants into 451 valid responses and partial least square structural equation modeling (PLS-SEM) using SmartPLS 4 have been administered for the analysis. Besides the insignificant effect of descriptive norms on buying intention and environmental concerns on purchasing behavior, other factors significantly impact purchase intention and actual buying behavior. This research witnesses a significant mediating role of buying intention. This research suggests that practitioners (i.e., marketers, government, policymakers, and environmental focus companies) develop strategies for public advertisement and launch a general message and campaigns both in urban and rural areas to prevent environmental sustainability and increases awareness related to organic consumption.